Dystonic Reactions in Children Caused by Metoclopramide - Casteels-van Daele, M. (1970)
Five cases of alarming dystonic reactions are reported in children receiving a normal dosage of metoclopramide, a new anti-emetic drug. The symptomatology consisted mainly of neck pain, torticollis, retrocollis, oculogyric crisis, and trismus, and patients were admitted with presumed diagnoses of encephalitis, meningitis, and tetanus. After discontinuing the drug, all symptoms disappeared completely. We believe that metoclopramide should be used with caution in paediatrics and that all doctors should be familiar with its possible bizarre side-effects.